Controlling spin current polarization through non-collinear antiferromagnetism - T. Nan (Nature Portfolio, 2020)
In the typical spin-hall effect, spin-current, charge current, and spin polarisation are all mutually perpendicular, a feature enforced by symmetry. Here, using an anti-ferromagnet with a triangular spin structure, the authors demonstrate a spin-hall effect without a perpendicular spin alignment.